Pre-breeding Diets in the Seahorse Hippocampus reidi: How Do They Affect Fatty Acid Profiles, Energetic Status and Histological Features in Newborn? - Planas, Miquel; Olivotto, Ike; González, María Jesús; Laurà, Rosaria; Angeletti, Carlo; Amici, Adolfo; Zarantoniello, Matteo (Frontiers in Marine Science, 2021)
Seahorses (Hippocampus spp.) are exceptional marine species considering their reproductive patterns and other features. Due to the iconic characteristics of these fishes, aquarium trade and research efforts have increased in the last years. Consequently, novel rearing techniques have been developed; however, there is a need for improvements on a series of issues, namely reproduction success enhancement. The tropical species Hippocampus reidi is the most traded seahorse but many aspects of breeding and its impact on the quality of neonates are still poorly understood. In the present study, we assessed the effects of two pre-breeding diets on newborn quality and viability considering biochemical characteristics, energetic status and ultrastructural aspects of muscular tissue. During the whole pre-breeding season (5 months), the breeders were fed on one of the following diets: M0 (adult non-enriched Artemia) and M5 (adult non-enriched Artemia + mysidaceans). From the onset of the reproduction period, all breeders were fed for 6 months on diet M5. Breeding success and energetic status (ATP, total adenylic nucleotides, AEC and NAD) of newborns resulted considerably enhanced in treatment M5. However, initial differences in neonates quality did not affect further newborn performance (survival and growth until day 7 after male’s pouch release) while gaining access to high-quality preys (copepods). Besides, morphological alterations in muscle tissue were not observed. The reproduction in the species followed a capital–income continuum pattern characterized by an initial mixed capital-income period (until 70-100 days since the onset of the breeding season) followed by an income breeding period with progressive exhaustion of body reserves, especially in M0-newborns. Interestingly, the effects of pre-breeding diets were also noticed in the second half of the breeding period. Our results seemed to indicate that the requirements in essential fatty acids in H. reidi are lower than in other seahorse species (e.g., H. guttulatus). Globally, the results achieved revealed that high-quality pre-breeding diets enhanced reproduction success and would likely result advantageous to improve newborn endurance in conditions of moderate starvation or sub-optimal feeding.